Positron emission tomography guided dose painting by numbers of lung cancer: Alanine dosimetry in an anthropomorphic phantom. (January 2022) - Papoutsis, Iosif; Skjei Knudtsen, Ingerid; Peter Skaug Sande, Erlend; Louni Rekstad, Bernt; Öllers, Michel; van Elmpt, Wouter; Røthe Arnesen, Marius; Malinen, Eirik
Highlights: DPBN was delivered to a phantom based on the anatomy of a lung cancer patient examined by FDG PET/CT prior to radiotherapy. Alanine dosimetry showed that DPBN can be delivered with high accuracy to the tumour in the anthropomorphic phantom. For regions outside the tumour, high correspondence between planned and delivered doses were also found. Positioning errors can lead to large deviations and potentially sub-optimal tumor doses. Abstract: Background and purpose: Dose painting by numbers (DPBN) require a high degree of dose modulation to fulfill the image-based voxel wise dose prescription. The aim of this study was to assess the dosimetric accuracy of 18 F-fluoro-2-deoxy-glucose positron emission tomography( 18 F-FDG-PET)-based DPBN in an anthropomorphic lung phantom using alanine dosimetry. Materials and methods: A linear dose prescription based on 18 F-FDG-PET image intensities within the gross tumor volume (GTV) of a lung cancer patient was employed. One DPBN scheme with low dose modulation (Scheme A; minimum/maximum fraction dose to the GTV 2.92/4.26 Gy) and one with a high modulation (Scheme B; 2.81/4.52 Gy) were generated. The plans were transferred to a computed tomograpy (CT) scan of a thorax phantom based on CT images of the patient. Using volumetric modulated arc therapy (VMAT), DPBN was delivered to the phantom with embedded alanine dosimeters. A plan was also delivered to an intentionally misaligned phantom. Absorbed doses at various points in the phantom were measured by alanine dosimetry. Results: A pointwise comparison between GTV doses from prescription, treatment plan calculation and VMAT delivery showed high correspondence, with a mean and maximum dose difference of <0.1 Gy and 0.3 Gy, respectively. No difference was found in dosimetric accuracy between scheme A and B. The misalignment caused deviations up to 1 Gy between prescription and delivery. Conclusion: DPBN can be delivered with high accuracy, showing that the treatment may be applied correctly from a dosimetric perspective. Still, misalignment may cause considerable dosimetric erros, indicating the need for patient immobilization and monitoring.